Synthesis of Branched Dithiotrisaccharides via Ring-Opening Reaction of Sugar Thiiranes - Repetto, Evangelina (2012)
Satisfactory procedures are described for the synthesis of 5,6- and 3,4-thiirane derivatives from the respective hexofuranose or hexopyranose epoxide precursors. The controlled ring-opening reaction of thiiranes by 1-thioaldoses was successfully accomplished to afford, region and stereoselectively, beta-S-(1-4)-3,4-dithiodisaccharides. For instance, the regioselective attack of per-O-acetyl-1-thioglucose to C-4 of 2-propyl 2,6-di-O-acetyl-3,4-epithio-alpha-D-galactopyranoside (14) gave the derivative of Glcp-beta-S-(1-4)-3,4- dithioGlcp-O-iPr (17). This thiodisaccharide was accompanied by the (1-3)-disulfide 18, formed between 16 and 17, and the symmetric (3-3)-disulfide 19, which resulted from the oxidative dimerization of 17. However, the S-acetyl derivative of 17 could be obtained in good yield (62%) by LiAlH4 reduction of the crude mixture 17−19, followed by acetylation. The same sequence of reactions starting from 14 and the 1-thiolate of Galp afforded the per-O,S-acetyl derivative of Galp-beta-S-(1-4)-3,4-dithio-alpha-D-Glcp-O-iPr (23), which was selectively S-deacetylated to give 25. The dithiosaccharides 17 and 25 are 3,4-di-S-analogues of derivatives of the natural disaccharides cellobiose and lactose, respectively. The ring-opening reaction of 5,6-epithiohexofuranoses of D-galacto (8) or L-altro (11) configuration with 1-thioaldoses was also regio- and stereoselective to give the respective beta-S-(1-6)-linked 5,6-dithiodisaccharides 26 or 29 in excellent yields. Glycosylation of the free thiol group of 17, 25, or 26, using trichloroacetimidates as glycosyl donors, led to the corresponding branched dithiotrisaccharides. Some of them are sulfur analogues of derivatives of branched trisaccharides found in natural polysaccharides.